2021
DOI: 10.3390/healthcare9020159
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study Examining Differences in Indication for Cesarean Delivery by Race/Ethnicity

Abstract: (1) Background: There are persistent racial/ethnic disparities in cesarean delivery in the United States (U.S.), yet the causes remain unknown. One factor could be provider bias. We examined medical indications for cesarean delivery that involve a greater degree of physician discretion (more subjective) versus medical indications that involve less physician discretion (more objective) to better understand factors contributing to the higher rate among Micronesian, one of the most recent migrant groups in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…For example, rates of cesarean delivery among Micronesian women are significantly higher compared to White women, even after adjusting for medical and sociodemographic confounders [19,20]. In addition, a study that compared indications for cesarean between Micronesian and White patients found that Micronesian women were over three times more likely to experience a cesarean delivery for more subjective medical indications (e.g., non-reassuring fetal heart tracing and arrest of labor) compared to more objective indications, a finding consistent with similar work examining cesarean delivery among Black women in the US [22,23]. These studies suggest that research into provider bias may help to clarify variables influencing clinical decision-making in the context of cesarean delivery and help to better understand the racial disparities observed [22,23].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…For example, rates of cesarean delivery among Micronesian women are significantly higher compared to White women, even after adjusting for medical and sociodemographic confounders [19,20]. In addition, a study that compared indications for cesarean between Micronesian and White patients found that Micronesian women were over three times more likely to experience a cesarean delivery for more subjective medical indications (e.g., non-reassuring fetal heart tracing and arrest of labor) compared to more objective indications, a finding consistent with similar work examining cesarean delivery among Black women in the US [22,23]. These studies suggest that research into provider bias may help to clarify variables influencing clinical decision-making in the context of cesarean delivery and help to better understand the racial disparities observed [22,23].…”
Section: Introductionsupporting
confidence: 69%
“…Similar to other racial minority groups, NHPIs and Micronesian communities specifically experience substantial disparities in health and healthcare outcomes [14][15][16][17]. Maternal and perinatal outcomes are no exception [18][19][20][21][22]. For example, rates of cesarean delivery among Micronesian women are significantly higher compared to White women, even after adjusting for medical and sociodemographic confounders [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Black childbearing people have twice the rate of cesareans compared with White and other groups due to non-reassuring fetal status, despite adjustments for medical, pregnancy, neonatal, and sociodemographic risks. 6,7,22,23 Non-reassuring fetal status has been considered a subjective indication for cesarean, 24 as it is based on clinician interpretation of fetal heart rate tracings and inter-rater reliability is poor. 25 A disproportionate diagnosis of non-reassuring fetal status may be related to practitioner bias, as noted in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…25 A disproportionate diagnosis of non-reassuring fetal status may be related to practitioner bias, as noted in previous studies. 23,24 For example, clinician beliefs about poorer birth outcomes for Black childbearing people may influence the interpretation of equivocal or intermediate fetal heart rate tracings, leading clinicians to intervene with cesarean sections sooner than they otherwise might. Interpersonal racism has the potential to affect clinician-client communication patterns, 2,26 and implicit and explicit racist beliefs may influence clinician decision-making and behaviors, 2 including the decision to proceed with cesarean birth.…”
Section: Discussionmentioning
confidence: 99%
“…Excess mortality among Black patients is best explained by hospital type (Black- showed that among nulliparous women birthing a term singleton in the vertex position (nulliparous, term, singleton, vertex), potentially modifiable maternal cardiometabolic risk factors (obesity, maternal hyperglycemia and hypertensive disorders) partially mediate some of this association between NSTV cesarean deliveries and race/ethnicity [30]. Provider implicit bias might account for at least some of the cesarean birth variance, and as such, presents yet another potential area for disparitytargeted improvement [31].…”
Section: Key Pointsmentioning
confidence: 99%